Dimensions of leisure for life - Tapps, Tyler Nicholas; Wells, Mary Sara; Parr, Mary 1962- (Human Kinetics, 2022)
"This book, aimed primarily at college students who are studying leisure, addresses the multiple ways leisure impacts lives and our larger society"--